Ultrasound-guided microwave ablation versus surgery for low-risk solitary papillary thyroid microcarcinoma: a propensity-matched cohort study - Yujie Ren; Yujiang Li; Xiaoqiu Chu; Guofang Chen; Xue Han; Yueting Zhao; Chao Liu; Jianhua Wang; Shuhang Xu (Endocrine Connections)
Objective: To evaluate the therapeutic effects of microwave ablation (MWA) versus surgery in treating low-risk papillary thyroid microcarcinoma (PTMC) and to assess recurrence-free survival (RFS) in patients with and without the BRAFV600E mutation. Methods: Between August 2016 and September 2022, 158 patients diagnosed with low-risk PTMC treated with MWA and 288 patients who underwent surgical treatment were retrospectively analyzed. All patients were followed-up for over a year. Local tumor progression (LTP), RFS and adverse events associated with both treatments were monitored. Following propensity score matching (PSM), comparisons were made regarding LTP, RFS, complications and treatment variables. Results: Prior to matching, MWA patients were younger than those in the surgery group (38 (30.75, 47) vs 43 (34, 50.75), P = 0.000). Tumors treated with MWA had smaller maximum diameters (5.7 (4.6, 7.0) vs 6.9 (5.8, 8.6), P = 0.000) and volumes (70.7 (35.2, 120.9) vs 122.0 (63.9, 228.8), P = 0.000). After 1:1 PSM, each group contained 141 patients with comparable baseline characteristics. During the follow-up, LTP developed in nine patients: six in the MWA group and three in the surgery group. There were no cases of distant metastasis or cancer-related deaths. Adjusting for age, sex, tumor location and largest diameter, there was no significant association between treatment modality and recurrence (HR = 3.75, 95% CI: 0.94–14.98, P = 0.062). There were no significant differences in RFS between patients with and without the BRAFV600E mutation in both groups (P = 0.45 and 0.74, respectively). Furthermore, the incidence of complications was comparable between treatments. Conclusion: Both MWA and surgical treatment offer similar efficacy and safety profiles for managing low-risk PTMC. MWA may represent a viable alternative to conventional surgical approaches, especially for patients harboring the BRAFV600E mutation.